STABL ISOTOPES AND HYDROCHEMICAL PARAMETER AS INDICATORS OF AL-RAZZAZA LAKE WATER INTERACTION WITH GROUNDWATER SURROUNDING / KARBALA GOVERNORATE- IRAQ. - Nada, K. B.; Salman, M. S.; Harpy, A. F; Ajeena, A R .; Falih, A .H. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
This research was aimed to study the exposure of Razzazah Lake to major hydrological changes in recent years as a result of natural climatic changes and drought, high evaporation in lake due to stop discharge from Habbaniyah Lake by Al- majera channel. During 2019, we collected surface water samples at three locations, and three samples from groundwater, in addition one samples from each location Imam Ali Drop and Sewage water of Karbala. The Results show that the heavy isotopes in lake and groundwater well are enriched during the warm period, and depleted during the cold period. Chemically, The dominant cations and anions in Al-Razzaza lake water are mainly of in Order Ca > Na > Mg and Cl>SO4 and the water type Ca-Chloride in both period. according to the ratio of Ca/Cl concentration in water samples in the study area, it can be see that same ratio of Ca/Cl between Al-Razzaz lake water and W1 well, this indicator to the interaction between them.